2013
DOI: 10.1111/pai.12032
|View full text |Cite
|
Sign up to set email alerts
|

Safety of mometasone furoate nasal spray in the treatment of nasal polyps in children

Abstract: Results of this study confirm the safety profile of MFNS in pediatric patients with bilateral nasal polyps over 4 months, even at double the recommended pediatric dosage for allergic rhinitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 29 publications
0
20
0
1
Order By: Relevance
“…Three of the included studies provided a description that suggested that adequate sequence generation was conducted (Chur 2013;Lund 1998;Stjarne 2006). Another three stated that the trials were randomised but did not provide further information, making them at an 'unclear' risk of bias (Filipovic 2006;Holmberg 1997;Johansen 1993).…”
Section: Sequence Generationmentioning
confidence: 99%
See 4 more Smart Citations
“…Three of the included studies provided a description that suggested that adequate sequence generation was conducted (Chur 2013;Lund 1998;Stjarne 2006). Another three stated that the trials were randomised but did not provide further information, making them at an 'unclear' risk of bias (Filipovic 2006;Holmberg 1997;Johansen 1993).…”
Section: Sequence Generationmentioning
confidence: 99%
“…However, we only considered the risk of both performance and detection bias to be low for five of the studies, with adequate measures to mask the type of treatment given ( Holmberg 1997;Lund 1998;Small 2005;Stjarne 2006). We rated blinding as inadequate (high risk of bias) in three studies, despite their being reported as 'double-blinded' studies (Chur 2013;Demirel 2008;Johansen 1993). The blinding was inadequate in these studies, as there was no placebo or 'dummy' used to account for differences in the number of times treatment was administered or methods of delivery.…”
Section: Blindingmentioning
confidence: 99%
See 3 more Smart Citations